The ice as leitmotif of a life: Erich von Drygalski, writings and photographs - Millar, P (Polar Record, 2019)
Professional scientist-geographer Erich von Drygalski led the first German expedition toAntarctica in 19011903. The expedition saw itself as purely scientific, which turned outto be at odds with the expectations of Imperial Germany at the time. It was one of the firstto use photography extensively and effectively to document and record scientific activitiesand to shape the publics image of the work that was being done in this remote and unknown part of the world. Ice was the leitmotif of Drygalskis life. He had prior experience in the Arctic, and the year spent in Antarctica confirmed his nuanced way of viewing the ice: on the one hand, and foremost, scholarly and objective, while still appreciating its aesthetic qualities; on the other, infused with feelings of human vulnerability. Using discourse analysis, this article examines Drygalskis published work and photographs he chose to illustrate it, in order to investigate what the ice meant to him. In his writings, it was the scholarly, objective attitude which predominated and this may have contributed to the generally lacklustre reception of his Antarctic achievements. The photographs he chose to illustrate his published work, however, were many and varied, often capturing the awe-inspiring beauty of the ice and contributing to good sales of his narrative of the South Polar Expedition.